Bladder Cancer Incidence in Iran: Results of the Iranian National Population-Based Cancer Registry from 2014 to 2016 - Partovipour, Elham; Roshandel, Gholamreza; Motlagh, Ali; Salavati, Fereshteh; Mohammadi, Gohar; Davanlou, Masoud; Asgari, Fereshteh; Khoshaabi, Mostafa; Raeisi, Alireza; Malekzadeh, Reza; et al. (Urology Journal, 2021)
Purpose: Bladder cancer is a common cancer in the world with the highest rates in Southern and Western Europe, North America, and Western Asia. It imposes a high economic burden to the health care system globally. The objective of this study is to provide the incidence of bladder cancer and its geographic distribution in Iran in 2014, 2015 and 2016. Results: We registered 5817, 5662 and 6630 new bladder cancer cases in 2014, 2015 and 2016, respectively with men counting 82% of cases in every year. The ASR of bladder cancer in total Iranian population was 8.50 (95% CI: 8.28-8.72), 8.05 (95% CI: 7.83-8.27) and 8.74 (95% CI: 8.52-8.96) per 100,000 in those years. The male to female ratio was 5 every year. Kerman has the highest ASR in each of the years, respectively 15.49, 13.07 and 12.46, and Ilam has the lowest ASR during 2014 to 2015, respectively 4.27 and 3.50, and Sistan and Baluchestan has the lowest rate in 2016 (ASR:3.56) in both sexes. Conclusion: The highest incidence of bladder cancer was observed in Central, southern and northwestern parts of Iran. Through the analysis of the incidence patterns and the identification of risk factors associated with it, steps can be taken towards prevention and control measures.